2020
DOI: 10.18632/oncotarget.27767
|View full text |Cite
|
Sign up to set email alerts
|

MEK is a promising target in the basal subtype of bladder cancer

Abstract: While many resources exist for the drug screening of bladder cancer cell lines in 2D culture, it is widely recognized that screening in 3D culture is more representative of in vivo response. Importantly, signaling changes between 2D and 3D culture can result in changes to drug response. To address the need for 3D drug screening of bladder cancer cell lines, we screened 17 bladder cancer cell lines using a library of 652 investigational small-molecules and 3 clinically relevant drug combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Cells were screened in 384-well ultra-low attachment plates (Corning, 4516 or S-Bio, MS-9384WZ) in singlicate or duplicate, 7-point dose–response format. Cells were plated in our previously defined SM+6 medium ( 30 ). Cells were plated on day 0 at 3,000 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were screened in 384-well ultra-low attachment plates (Corning, 4516 or S-Bio, MS-9384WZ) in singlicate or duplicate, 7-point dose–response format. Cells were plated in our previously defined SM+6 medium ( 30 ). Cells were plated on day 0 at 3,000 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an underlying enzyme named as Ubiquitin C-terminal hydrolase L5 (UCHL5) was suggested to be a contributing factor for tumor growth progression and metastasis occurrence in multiple cancer tumors as endometrial cancer (EC). To identify the role of UCHL5 on EC, bioinformatics analysis revealed that UCHL5 overexpression in EC tissues lead to lower overall survival (Merrill et al, 2020[ 105 ]). Hence, UCHL5 was seen to be reversibly associated with the 26S proteasome in order to prevent target proteins degradation by hydrolyzing ubiquitin chains (Rastogi and Mishra, 2012[ 126 ]).…”
Section: Btz Implementation In Solid Tumorsmentioning
confidence: 99%